PRAGMATICIST HOLISM AND MORAL INTEGERITY: A Study on the Ethical Dimensions of the Pragmaticism of Charles Sanders Peirce - Vadakkemuriyil, Abraham Joseph (Asian Horizons, 2011)
Charles Sanders Peirce, one of the greatest intellectualists that America has ever produced, introduced Pragmatism as a system of philosophy to the American philosophers and later classified it as Pragmaticism to distinguish it from popular interpretations. The basic theoretical stand of Peirce is expressed in his famous pragmatic maxim which is a tool for scientific study; first, when a concept appears to be clear, it can be further explored whether this concept is true or false. This means that the action which tests and clarifies the meaning of a belief is not the end of the inquiry, but it is only a starting point for further thought looking for the final opinion of the community of inquirers where particular individual opinions are only contributions to the final opinion of such a larger community. The clarification of doubt is not just the individual’s responsibility alone, but is also a prerogative of the community to ensure rightness of the individual’s actions to bring about the maximum good. Good reasoning depends on good habits of the mind. One such habit which, without being fully aware of, we employ in our everyday living is our hypothesis of Reality, the guiding principle of all our reasoning.